Islamic banking and finance in Malaysia: an evaluation from the perspective of Maqasid al-Shari`ah - Abdullah @ Chuah Hock Leng, Osman; Sayadat, Muhammad Nazmus (2015)
Riba is haram in Islam. In the past, conventional banks use riba as a mechanism to charge borrowers. This is a great problem for Muslims throughout the world. However, in Malaysia, the Pilgrimage Management and Fund Board was established in 1962to collect money from Muslims to finance their trip to Makkah to perform al-haj. In 1983, in addition to the collection of funds from Muslims for the trip to Makkah, Islamic banks implementing finance in all services similar to conventional banks were set up. After more than three decades, with Islamic banks making good profit nearly every year, all conventional banks in Malaysia are emulating Bank Islam Malaysia Berhad to set up Islamic banks with no riba in their banking services. The Islamic banks now offer services that comply with the rules and regulations of Islam. Thus, the purpose of this paper is to evaluate the challenges faced by Islamic banks in Malaysia and their solutions for the benefit of the Ummah. This paper also identifies the issues and makes recommendations for these Islamic banks.